2017
DOI: 10.1002/cne.24203
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemistry of neurons in the ventrolateral medulla activated by hypotension: Are the same neurons activated by glucoprivation?

Abstract: Previous studies have demonstrated that a range of stimuli activate neurons, including catecholaminergic neurons, in the ventrolateral medulla. Not all catecholaminergic neurons are activated and other neurochemical content is largely unknown hence whether stimulus specific populations exist is unclear. Here we determine the neurochemistry (using in situ hybridization) of catecholaminergic and noncatecholaminergic neurons which express c-Fos immunoreactivity throughout the rostrocaudal extent of the ventrolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
2
10
0
Order By: Relevance
“…No information was provided about cross‐reactivity with the protein product of FRA1. In further confirmation of the specificity of sc‐253, we have found that this antibody shows a distribution of 2DG‐activated C1 and C3 neurons in rats (Korim, Llewellyn‐Smith, & Verberne, ; Menuet et al, ) that is very similar to the distribution of 2DG‐responsive neurons localized with an Arnel anti‐Fos antiserum that we have used previously (Ritter et al, ) and to the distribution detected by others with a different SCBT anti‐Fos that was raised against amino acids 3–16 of the protein encoded by human c‐fos (Parker et al, ; Parker et al, ). Staining with SCBT anti‐Fos sc‐253 also reveals virtually the same distribution of hypotension‐responsive C1 neurons in normotensive WKY rats as our sheep anti‐Fos (Minson, Arnolda, Llewellyn‐Smith, Pilowsky, & Chalmers, ) and produces a similar staining pattern to other anti‐Fos antisera that have been used for functional neuroanatomical studies on barosensitive C1 neurons in rats (e.g., Chan & Sawchenko, ; Stornetta, Sevigny, Schreihofer, Rosin, & Guyenet, ; Sved, Mancini, Graham, Schreihofer, & Hoffman, ).…”
Section: Methodssupporting
confidence: 79%
See 4 more Smart Citations
“…No information was provided about cross‐reactivity with the protein product of FRA1. In further confirmation of the specificity of sc‐253, we have found that this antibody shows a distribution of 2DG‐activated C1 and C3 neurons in rats (Korim, Llewellyn‐Smith, & Verberne, ; Menuet et al, ) that is very similar to the distribution of 2DG‐responsive neurons localized with an Arnel anti‐Fos antiserum that we have used previously (Ritter et al, ) and to the distribution detected by others with a different SCBT anti‐Fos that was raised against amino acids 3–16 of the protein encoded by human c‐fos (Parker et al, ; Parker et al, ). Staining with SCBT anti‐Fos sc‐253 also reveals virtually the same distribution of hypotension‐responsive C1 neurons in normotensive WKY rats as our sheep anti‐Fos (Minson, Arnolda, Llewellyn‐Smith, Pilowsky, & Chalmers, ) and produces a similar staining pattern to other anti‐Fos antisera that have been used for functional neuroanatomical studies on barosensitive C1 neurons in rats (e.g., Chan & Sawchenko, ; Stornetta, Sevigny, Schreihofer, Rosin, & Guyenet, ; Sved, Mancini, Graham, Schreihofer, & Hoffman, ).…”
Section: Methodssupporting
confidence: 79%
“…These results are consistent with the conclusion that RVLM non‐C1 neurons do not respond to insulin treatment and therefore may not play a significant role in glucoregulatory responses. In contrast, Parker et al have reported that treatment with 2DG induces Fos synthesis in a significant number of non‐C1 neurons (Parker et al, ; Parker et al, ). There are several possible methodological causes for the divergence between our Fos results with insulin and those of Parker et al with 2DG.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations